Human Immunodeficiency Virus and Pulmonary Arterial Hypertension - Mirrakhimov, Aibek E. (Hindawi Publishing Corporation, 2013)
Human immunodeficiency virus- (HIV-) related pulmonary arterial hypertension (PAH) is a rare complication of HIV infection. The pathophysiology of HIV-related PAH is complex, with viral proteins seeming to play the major role. However, other factors, such as coinfection with other microorganisms and HIV-related systemic inflammation, might also contribute. The clinical presentation of HIV-related PAH and diagnosis is similar to other forms of pulmonary hypertension. Both PAH-specific therapies and HAART are important in HIV-related PAH management. Future studies investigating the pathogenesis are needed to discover new therapeutic targets and treatments.